Dynamic Simulation and Modeling of a Novel Combined Hybrid Photovoltaic-Thermal Panel Hybrid System - Sami, S; Campoverde, C (International Journal of Sustainable Energy and Environmental Research, 2018)
A novel combined concept and simulation model of a hybrid photovoltaic-thermal solar panel hybrid system are presented. This concept is developed to enhance the energy conversion efficiency of the PV cell and utilize excess thermal energy dissipated by the conversion process to produce domestic hot water. A heat transfer and fluid flow two dimensional dynamic model was developed to describe the behavior of a combined photovoltaic cell-thermal panel hybrid system under different solar irradiance, material properties, and boundary conditions. The model is based on dynamic mass and energy equations coupled with the heat transfer coefficients, and thermodynamic constants as well as material properties.